Dmab/ivDde protected diaminodiacids for solid-phase synthesis of peptide disulfide-bond mimics. Issue 17 (26th April 2017) - Xu, Yang; Wang, Tao; Guan, Chao-Jian; Li, Yi-Ming; Liu, Lei; Shi, Jing; Bierer, Donald
Graphical abstract: Highlights: A new diaminodiacid containing Dmab/ivDde protecting groups has been prepared. The new diaminodiacid was used to successfully prepare an oxytocin disulfide mimetic. Dmab/ivDde protecting groups avoid the use of heavy metal reagents during cleavage. Abstract: The use of pre-prepared diaminodiacids has been established as an effective approach for the chemical synthesis of peptide disulfide bond mimics. A technical problem often encountered in the implementation of the diaminodiacids strategy is the use of heavy metal reagents to remove the side-chain protecting groups. In the present work, we reported the development of diaminodiacid that carry 4-( N -[1-(4, 4-dimethyl-2, 6-dioxocyclo-hexylidene)-3-methylbutyl]amino)benzyl (Dmab) and 1-(4, 4-dimethyl-2, 6-dioxocyclohex-1-ylidene)-3-methylbutyl (ivDde) protecting groups. This pair of protecting groups can be readily removed by mild hydrazinolysis during the solid-phase synthesis on resin. We demonstrated the use of Dmab/ivDde protected diaminodiacids in the successful synthesis of a disulfide surrogate of oxytocin.